Peran Employee Engagement sebagai Variabel Mediasi Studi Pengaruh Talent Management terhadap Kinerja Karyawan pada PT. Oscarmas Heavy Equipment - Syael Mirsandi; Shofia Amin; Besse Wediawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Competition in this world is getting tighter, including in the business world, this is due to the large number of companies competing to dominate market share, because globalization is a challenge for business people to maintain the opportunities they have and obtain or achieve new opportunities. The topic of employee performance has become a concern among academics in the last decade. The main reason is that employee performance is closely related to organizational productivity and achievement and vice versa. Increasing employee performance can be driven by talent management. Apart from talent management, another factor in efforts to improve employee performance is Employee Engagement. This research is quantitative research using a survey research design. The sample in this study consisted of 100 employees of PT. Oscarmas Heavy Equipment taken through Purposive Sampling Technique. The data collection instrument is a questionnaire with a Likert Scale format consisting of five alternative answers. Data from filling out the questionnaire will be analyzed using the Partial Least Square (PLS) technique. The research results show that the Talent Management variable has a significant influence on Employee Engagement and Employee Performance, the Employee Engagement variable has a significant influence on Employee Performance and the Employee Engagement variable is able to mediate the Talent Management variable on Employee Performance.